Mentoring dynamics: roles, personalities, moderators and outcomes in military and civilian academic training settings - Shaffer, Gregory T., author; Hautaluoma, Jacob E., advisor (Colorado State University. Libraries, 2003)
The present study investigated mentoring processes and outcomes across two diverse settings including a short-term formal mentoring program at an undergraduate military training institution between military officers and young military leaders, and longer-term relationships between students and faculty in a graduate school environment at a civilian university. Using data from 272 mentor and protégé respondents referring to 200 mentoring relationship dyads, satisfaction and performance outcomes were linked to mentor and protégé personality dimensions, mentor roles, time spent in mentoring, and mentoring setting. Results suggest that personality dimensions and mentor roles exhibit separate main effects on mentor and protégé satisfaction with mentoring relationships and with protégé performance outcomes, and that time spent in mentoring moderates several of these relationships. Protégé conscientiousness was the most noticeable personality variable in the overall model, relating positively to protégé performance, protégé and mentor satisfaction with mentoring, time invested in mentoring and mentor roles. Mentor openness yielded positive relationships with protégé performance, mentor roles, and time invested in mentoring. Protégé extraversion was positively linked to protégé satisfaction with the department and to mentor roles, but mentor extraversion negatively related to time invested in mentoring. In spite of large contextual differences between mentoring programs in the two settings, including differences in specific roles played by mentors, the relationships between overall mentor role strength and positive mentoring outcomes did not vary by setting. Implications for mentoring practice and research are discussed.
Keywords: personality; social psychology; personality psychology